MENINGKATKAN HASIL BELAJAR SISWA MELALUI METODE PEMBELAJARAN PROBLEM SOLVING PADA MATERI KONSEP MOL DI KELAS X-3 MAN RUKOH BANDA ACEH - Rosniar Rosniar; Salawati Salawati (UIN AR-RANIRY, 2018)
The aim of this study was to improve the learning achievement and activities of students through the implementation of the Problem Solving learning method in Mol Concept. This study was conducted by using two cycles of classroom action research. The subject of this research was 25 students of class X-2 MAN Rukoh Banda Aceh. The result of the implementation of learning Problem Solving method showed that there is improvement of student learning achievement from Cycle I to Cycle II. It could be seen from the results of research that showing about 64% of students had passed learning in Cycle I and about 88% in Cycle II. While the observation was conducted, the improvement of learning activities of students amounts 50%. Based the result of this study, it is can be concluded that the implementation of learning Problem Solving method can improve the learning achievement and activities of the student in Mol Concept.